Prepreg, its manufacturing method, and molded body

JP2023027140A5Inactive Publication Date: 2025-01-30MITSUBISHI CHEM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022190382
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-25
Filing Date
2022-11-29
Publication Date
2025-01-30
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing prepregs using amorphous thermoplastic resins as matrix resins face challenges in maintaining mechanical properties when exposed to chemicals such as hydraulic oil, necessitating improved chemical resistance and mechanical integrity.

Method used

A prepreg formulation utilizing a polyetherimide resin with specific tensile elongation retention properties and a blend of polyetherimide resins with varying melt volume rates, combined with carbon fibers, to enhance chemical resistance and mechanical strength.

Benefits of technology

The prepreg achieves high chemical resistance and mechanical properties, maintaining strength even after exposure to hydraulic oil, ensuring robust performance in applications like aircraft and automobiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2023027140000001
    Figure 2023027140000001
  • Figure 2023027140000002
    Figure 2023027140000002
  • Figure 2023027140000003
    Figure 2023027140000003
Patent Text Reader

Abstract

One object of the present invention is to provide a fiber-reinforced thermoplastic resin prepreg that can obtain a molded article having excellent chemical resistance and mechanical properties while using an amorphous thermoplastic resin as a matrix resin, a method for producing the same, and a molded article. The prepreg comprises a matrix resin containing a polyetherimide resin (A) having a repeating unit represented by the following general formula (a), and carbon fibers, wherein the matrix resin satisfies the following condition (1): Condition (1): The matrix resin is extruded into a film, and the tensile elongation at break (T1) in the TD direction of the film and the tensile elongation at break (T2) in the TD direction of the film after immersion in a specific oil liquid at 23°C for 1000 hours are measured. The tensile elongation retention rate calculated from T1 and T2 is 15% or more and 90% or less. TIFF2023027140000017.tif35170 m: Number of 5 to 1500
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a prepreg, a method for manufacturing the same, and a molded article. This application claims priority based on Japanese Patent Application No. 2021-029143, filed in Japan on February 25, 2021, and the contents of that application are incorporated herein by reference. [Background technology]

[0002] Engineering plastics, such as crystalline nylon 66 (PA66) resin and amorphous polycarbonate (PC) resin, have excellent heat resistance and mechanical strength and are widely used as industrial parts. Furthermore, super engineering plastics, such as crystalline polyetheretherketone (PEEK) resin and amorphous polyetherimide (PEI) resin, possess even greater heat resistance and mechanical strength than engineering plastics, and their application as a substitute for metal parts is progressing.

[0003] To further expand the application range of engineering plastics and super engineering plastics, fiber-reinforced composite materials have been proposed in which matrix resins containing these materials are reinforced with reinforcing fibers. For example, Patent Documents 1 and 2 disclose fiber-reinforced composite materials such as prepregs that use amorphous thermoplastic resin as the matrix resin. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2004-107626 [Patent Document 2] Japanese Patent Publication No. 2005-239843 [Overview of the project] [Problems that the invention aims to solve]

[0005] When molded parts made from prepregs are used in aircraft, automobiles, and other applications, chemicals such as hydraulic fluid may adhere to the molded parts, and it is required that the mechanical properties can be maintained even when chemicals adhere to them.

[0006] One of the objectives of the present invention is to provide a fiber-reinforced thermoplastic resin prepreg, a method for producing the same, and a molded article, which can be obtained by using an amorphous thermoplastic resin as the matrix resin, while still yielding a molded article with excellent chemical resistance and mechanical properties. [Means for solving the problem]

[0007] The present invention has the following aspects. [1] A matrix resin comprising a polyetherimide resin (A) having repeating units represented by the following general formula (a), and carbon fibers, A prepreg in which the matrix resin satisfies the following condition (1). Condition (1) (i) The matrix resin is extruded into a film to produce a film, (ii) The tensile elongation at break (T1) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (iii) Separately, the film prepared in (i) above is immersed in an oil solution containing 55-65% by mass of tributyl phosphate at 23°C for 1000 hours, and then the tensile elongation at break (T2) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (iv) The tensile elongation retention ratio, calculated from the following formula (1), is 15% or more and 90% or less. Tensile elongation retention rate = (Tensile elongation at break (T2) / Tensile elongation at break (T1)) × 100 ... (1)

[0008] [ka]

[0009] In equation (a), m is a number between 5 and 1500. [2] The polyetherimide resin (A) has a melt volume rate of 3 to 10 cm³ at a set temperature of 360°C and a load of 5 kg, as measured in accordance with ISO 1133. 3 The prepreg according to [1], comprising a polyetherimide resin (A-1) which is 10 min. [3] The prepreg according to [2], wherein the content of the polyetherimide resin (A-1) is 85% by mass or more relative to the total mass of the matrix resin. [4] The prepreg according to [2] or [3], wherein the content of the polyetherimide resin (A-1) is 95% by mass or less with respect to the total mass of the matrix resin. [5] The polyetherimide resin (A) has a melt volume rate of 15-30 cm³ at a set temperature of 360°C and a load of 5 kg, as measured in accordance with ISO 1133. 3 A prepreg according to any one of items [1] to [4], comprising a polyetherimide resin (A-2) which is 10 min. [6] The prepreg according to [5], wherein the content of the polyetherimide resin (A-2) is 5% by mass or more relative to the total mass of the matrix resin. [7] The prepreg according to [5] or [6], wherein the content of the polyetherimide resin (A-2) is 15% by mass or less with respect to the total mass of the matrix resin. [8] The prepreg according to any one of [1] to [7], wherein the carbon fibers are continuous fibers. [9] The prepreg according to any one of [1] to [8], wherein m is preferably a number between 10 and 1000, more preferably between 50 and 800, and even more preferably between 100 and 600, in formula (a).

[10] The prepreg according to any one of [1] to [9], wherein the tensile elongation retention rate is preferably 20% or more and 90% or less, more preferably 30% or more and 90% or less, even more preferably 50% or more and 90% or less, and more preferably 70% or more and 90% or less.

[11] The weight content of the matrix resin in the prepreg is preferably 15 to 70% by weight, more preferably 20 to 60% by weight, still more preferably 25 to 45% by weight, and is the prepreg according to any one of [1] to

[10] .

[12] The volume content (Vf) of carbon fiber in the prepreg is preferably 20 to 75% by volume, more preferably 30 to 70% by volume, still more preferably 45 to 65% by volume with respect to the total volume of the prepreg, and is the prepreg according to any one of [1] to

[11] .

[13] The content of the polyetherimide resin (A-1) is preferably 30% by mass or more and 100% by mass or less, more preferably 50% by mass or more and 95% by mass or less, still more preferably 70% by mass or more and 95% by mass or less with respect to the total mass of the matrix resin, and is the prepreg according to any one of [2] to

[12] .

[14] The content of the polyetherimide resin (A-2) is preferably 0% by mass or more and 70% by mass or less, more preferably 5% by mass or more and 50% by mass or less, still more preferably 5% by mass or more and 30% by mass or less with respect to the total mass of the matrix resin, and is the prepreg according to any one of [5] to

[13] .

[15] The glass transition temperature (Tg) of the polyetherimide resin (A-1) is preferably 50 to 500 °C, more preferably 100 to 300 °C, still more preferably 150 to 250 °C, and is the prepreg according to any one of [2] to

[14] .

[16] The glass transition temperature (Tg) of the polyetherimide resin (A-2) is preferably 50 to 500 °C, more preferably 100 to 300 °C, still more preferably 150 to 250 °C, and is the prepreg according to any one of [5] to

[15] .

[17] The matrix resin contains a polyetherimide resin (A) having two or more repeating units represented by the following general formula (a) with different melt volume rates measured in accordance with ISO 1133 at a set temperature of 360 °C and a load of 5 kg. The difference in melt volume rate represented by [melt volume rate of the first polyetherimide resin] - [melt volume rate of the second polyetherimide resin] is preferably 5 to 27, more preferably 7 to 20, still more preferably 10 to 15, and is the prepreg according to any one of [1] to

[16] .

[18] The polyetherimide resin (A) has a melt volume rate of 3 to 10 cm 3 / 10 min at a set temperature of 360 °C and a load of 5 kg measured in accordance with ISO 1133, and a melt volume rate of 15 to 30 cm 3 / 10 min at a set temperature of 360 °C and a load of 5 kg measured in accordance with ISO 1133, and contains a polyetherimide resin (A-2), The difference in glass transition temperature represented by [glass transition temperature of the polyetherimide resin (A-2)] - [glass transition temperature of the polyetherimide resin (A-1)] is preferably 0 to 20 °C, more preferably 0 to 10 °C, still more preferably 0 to 5 °C, and is the prepreg according to any one of [1] to

[17] .

[19] The matrix resin may contain a polyetherimide resin (B) other than the polyetherimide resin (A). The content of the polyetherimide resin (B) is preferably 0% by mass or more and 5% by mass or less, more preferably 0% by mass or more and 1% by mass or less, still more preferably 0% by mass or more and 0.5% by mass or less, and particularly preferably substantially not contained (that is, 0% by mass), and is the prepreg according to any one of [1] to

[18] .

[20] The proportion of the repeating unit represented by the general formula (a) in 100% by mass of the polyetherimide resin (A) is preferably 50 to 100% by mass, more preferably 70 to 100% by mass, still more preferably 95 to 100% by mass, and particularly preferably 100% by mass, and is the prepreg according to any one of [1] to

[19] .

[21] The prepreg according to any one of [1] to

[20] , wherein the 90° bending strength measured by the method described in the Examples is preferably 80 to 150 MPa, more preferably 90 to 130 MPa, and even more preferably 100 to 120 MPa.

[22] The prepreg according to any one of [1] to

[21] , wherein the in-plane shear strength retention rate measured by the method described in the Examples is preferably 70 to 100%, more preferably 80 to 100%, and even more preferably 90 to 100%.

[0010]

[23] A molded body obtained by molding a prepreg as described in any one of the items [1] to

[22] .

[0011]

[24] A method for producing a prepreg, comprising heating a laminate obtained by laminating a film containing an amorphous thermoplastic resin onto a carbon fiber substrate to impregnate the carbon fiber substrate with the amorphous thermoplastic resin, wherein the film satisfies the following condition (1a). Condition (1a) (v) The tensile elongation at break (T1) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (vi) Separately, the film is immersed in an oil solution containing 55-65% by mass of tributyl phosphate at 23°C for 1000 hours, and then the tensile elongation at break (T2) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (vii) The tensile elongation retention rate, calculated from the following formula (1), is 70% or higher. Tensile elongation retention rate = (Tensile elongation at break (T2) / Tensile elongation at break (T1)) × 100 ... (1)

[25] The method for producing a prepreg according to

[24] , wherein the carbon fiber substrate is a sheet-like bundle of carbon fibers in which carbon fibers are aligned in one direction.

[26] A method for producing a prepreg according to

[24] or

[25] , wherein the amorphous thermoplastic resin comprises a polyetherimide resin.

[27] The method for producing a prepreg according to

[26] , wherein the polyetherimide resin comprises a polyetherimide resin (A) having repeating units represented by the following general formula (a).

[0012] [ka]

[0013] In equation (a), m is a number between 5 and 1500.

[28] The method for producing a prepreg according to

[27] , wherein the content of the polyetherimide resin (A) is 85% by mass or more with respect to the total mass of the amorphous thermoplastic resin.

[29] The method for producing a prepreg according to any one of the articles

[24] to

[28] , wherein the amorphous thermoplastic resin is composed of two or more of the polyetherimide resins (A) with different melt volume rates measured in accordance with ISO 1133 at a set temperature of 360°C and a load of 5 kg.

[30] A method for producing a prepreg according to any one of the items [1] to

[22] .

[0014]

[31] A prepreg comprising a matrix resin and carbon fibers, The matrix resin is a prepreg comprising two or more polyetherimide resins (A) having repeating units represented by the following general formula (a), each having a different melt volume rate at a set temperature of 360°C and a load of 5 kg, as measured in accordance with ISO 1133.

[0015] [ka]

[0016] In equation (a), m is a number between 5 and 1500.

[32] The matrix resin has a melt volume rate of 10 cm³ at a set temperature of 360°C and a load of 5 kg, as measured in accordance with ISO 1133. 3A polyetherimide resin (A-1) having repeating units represented by the following general formula (a) with a melt volume rate of 15 cm³ at a set temperature of 360°C and a load of 5 kg, as measured in accordance with ISO 1133. 3 The prepreg according to

[31] , comprising a polyetherimide resin (A-2) having repeating units represented by the following general formula (a) for 10 minutes or more.

[0017] [ka]

[0018] In equation (a), m is a number between 5 and 1500.

[33] The prepreg according to either

[31] or

[32] , wherein a sheet-like bundle of carbon fibers, in which the carbon fibers are aligned in one direction, is impregnated with the matrix resin.

[34] The prepreg according to any one of

[31] to

[33] , wherein m is preferably a number between 10 and 1000, more preferably between 50 and 800, and even more preferably between 100 and 600, in formula (a).

[35] The prepreg according to any one of

[31] to

[34] , wherein the matrix resin has a tensile elongation retention rate measured by the method described in the Examples of 15% or more and 90% or less, preferably 20% or more and 90%, more preferably 30% or more and 90%, even more preferably 50% or more and 90%, and more preferably 70% or more and 90% or less.

[36] The weight content of the matrix resin in the prepreg is preferably 25 to 80% by weight, more preferably 30 to 70% by weight, and even more preferably 35 to 55% by weight, according to any one of

[31] to

[35] .

[37] The prepreg according to any one of

[31] to

[36] , wherein the volume content (Vf) of carbon fibers in the prepreg is preferably 20 to 75 volume%, more preferably 30 to 70 volume%, and even more preferably 45 to 65 volume%, based on the total volume of the prepreg.

[38] The prepreg according to any one of

[32] to

[37] , wherein the content of the polyetherimide resin (A-1) is preferably 30% by mass or more and 100% by mass or less, more preferably 50% by mass or more and 95% by mass or less, and more preferably 70% by mass or more and 95% by mass or less, based on the total mass of the matrix resin.

[39] The prepreg according to any one of

[32] to

[38] , wherein the content of the polyetherimide resin (A-2) is preferably 0% by mass or more and 70% by mass or less, more preferably 5% by mass or more and 50% by mass or less, and even more preferably 5% by mass or more and 30% by mass or less, based on the total mass of the matrix resin.

[40] The glass transition temperature (Tg) of the polyetherimide resin (A-1) is preferably 50 to 500°C, more preferably 100 to 300°C, and even more preferably 150 to 250°C, as described in any one of

[32] to

[39] .

[41] The glass transition temperature (Tg) of the polyetherimide resin (A-2) is preferably 50 to 500°C, more preferably 100 to 300°C, and even more preferably 150 to 250°C, as described in any one of

[32] to

[40] .

[42] The difference in melt volume rates expressed as [melt volume rate of the polyetherimide resin (A-2)] - [melt volume rate of the polyetherimide resin (A-1)] is preferably 5 to 27, more preferably 7 to 20, and even more preferably 10 to 15, according to any one of

[32] to

[41] .

[43] The prepreg according to any one of

[32] to

[42] , wherein the difference in glass transition temperatures expressed as [glass transition temperature of the polyetherimide resin (A-2)] - [glass transition temperature of the polyetherimide resin (A-1)] is preferably 0 to 20°C, more preferably 0 to 10°C, and even more preferably 0 to 5°C.

[44] The matrix resin may contain a polyetherimide resin (B) other than the polyetherimide resin (A), and the content of the polyetherimide resin (B) is preferably 0% by mass or more and 5% by mass or less, more preferably 0% by mass or more and 1% by mass or less, even more preferably 0% by mass or more and 0.5% by mass or less, and particularly preferably substantially none (i.e., 0% by mass), according to any one of

[31] to

[43] .

[45] The prepreg according to any one of

[32] to

[44] , wherein the proportion of repeating units represented by the general formula (a) in 100% by mass of the polyetherimide resin (A-1) is preferably 50 to 100% by mass, more preferably 70 to 100% by mass, even more preferably 95 to 100% by mass, and particularly preferably 100% by mass.

[46] The prepreg according to any one of

[31] to

[45] , wherein the 90° bending strength measured by the method described in the Examples is preferably 80 to 150 MPa, more preferably 90 to 130 MPa, and even more preferably 100 to 120 MPa.

[47] The prepreg according to any one of

[31] to

[48] , wherein the in-plane shear strength retention rate measured by the method described in the Examples is preferably 70 to 100%, more preferably 80 to 100%, and even more preferably 90 to 100%.

[48] ​​The prepreg according to any one of

[31] to

[47] , wherein the content of the polyetherimide resin (A) is 85% by mass or more with respect to the total mass of the matrix resin.

[0019] A molded body obtained by molding a prepreg as described in any one of the items

[49]

[31] to

[48] .

[0020]

[50] The method for producing a prepreg according to any one of

[31] to

[48] .

[0021]

[51] A resin composition containing two or more polyetherimide resins (A) having repeating units represented by the following general formula (a) and having different melt volume rates at a set temperature of 360 ° C. and a load of 5 kg measured in accordance with ISO 1133. [Chemical formula]

[0022] In the formula (a), m is a number from 5 to 1500.

[52] The resin composition according to

[51] , wherein the polyetherimide resin (A) is a polyetherimide resin (A-1) having a melt volume rate of 3 to 10 cm 3 / 10 min at a set temperature of 360 ° C. and a load of 5 kg measured in accordance with ISO 1133.

[53] The resin composition according to

[52] , wherein the blending amount of the polyetherimide resin (A-1) is 85% by mass or more based on the total mass of the resin composition.

[54] The resin composition preferably contains a polyetherimide resin (A-1) having repeating units represented by the following general formula (a) and having a melt volume rate of 10 cm or less at a set temperature of 360 ° C. and a load of 5 kg measured in accordance with ISO 1133, and a polyetherimide resin (A-2) having repeating units represented by the following general formula (a) and having a melt volume rate of 15 cm or more at a set temperature of 360 ° C. and a load of 5 kg measured in accordance with ISO 1133; preferably consisting essentially of the polyetherimide resin (A-1) and the polyetherimide resin (A-2); preferably consisting of the polyetherimide resin (A-1) and the polyetherimide resin (A-2), the resin composition according to any one of

[51] to

[53] .

[0023] ​​​ [ka]

[0024] In equation (a), m is a number between 5 and 1500. A film comprising the resin composition described in any one of the items

[55]

[51] to

[54] .

[56] Use of any one of the resin compositions described in

[51] to

[54] as a matrix resin in the production of prepregs.

[57] Use of the films described in

[55] in the manufacture of prepregs.

[0025] Furthermore, the present invention has the following aspects. [1] A matrix resin comprising a polyetherimide resin (A) having repeating units represented by the following general formula (a), and carbon fibers, A fiber-reinforced thermoplastic resin prepreg in which the matrix resin satisfies the following condition (1). Condition (1) (i) The matrix resin is extruded into a film to produce a film, (ii) The tensile elongation at break (T1) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (iii) Separately, the film prepared in (i) above is immersed in an oil solution containing 55-65% by mass of tributyl phosphate at 23°C for 1000 hours, and then the tensile elongation at break (T2) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (iv) The tensile elongation retention rate, calculated from the following formula (1), is 70% or higher. Tensile elongation retention rate = (Tensile elongation at break (T2) / Tensile elongation at break (T1)) × 100 ... (1)

[0026] [ka]

[0027] In equation (a), m is a number between 5 and 1500.

[0028] [2] The polyetherimide resin (A) has a melt volume rate of 3 to 10 cm² as measured in accordance with ISO 1133. 3 A fiber-reinforced thermoplastic resin prepreg of [1] comprising a polyetherimide resin (A-1) which is 10 min. [3] The fiber-reinforced thermoplastic resin prepreg according to [2], wherein the content of the polyetherimide resin (A-1) is 85% by mass or more relative to the total mass of the matrix resin. [4] The fiber-reinforced thermoplastic resin prepreg according to [2] or [3], wherein the content of the polyetherimide resin (A-1) is 95% by mass or less relative to the total mass of the matrix resin. [5] The polyetherimide resin (A) has a melt volume rate of 15-30 cm² as measured in accordance with ISO 1133. 3 A fiber-reinforced thermoplastic resin prepreg of any of the above [1] to [4], comprising a polyetherimide resin (A-2) which is 10 min / min. [6] The fiber-reinforced thermoplastic resin prepreg according to [5], wherein the content of the polyetherimide resin (A-2) is 5% by mass or more relative to the total mass of the matrix resin. [7] The fiber-reinforced thermoplastic resin prepreg according to [5] or [6], wherein the content of the polyetherimide resin (A-2) is 15% by mass or less relative to the total mass of the matrix resin. [8] A fiber-reinforced thermoplastic resin prepreg of any of the above [1] to [7], wherein the carbon fibers are continuous fibers. [9] A molded article obtained by molding any of the fiber-reinforced thermoplastic resin prepregs described in [1] to [8] above.

[0029]

[10] A matrix resin comprising an amorphous thermoplastic resin and carbon fibers, A fiber-reinforced thermoplastic resin prepreg in which the matrix resin satisfies the following condition (1). Condition (1) (i) The matrix resin is extruded into a film to produce a film, (ii) The tensile elongation at break (T1) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (iii) Separately, the film prepared in (i) above is immersed in an oil solution containing 55-65% by mass of tributyl phosphate at 23°C for 1000 hours, and then the tensile elongation at break (T2) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (iv) The tensile elongation retention rate, calculated from the following formula (1), is 70% or higher. Tensile elongation retention rate = (Tensile elongation at break (T2) / Tensile elongation at break (T1)) × 100 ... (1)

[11] A method for producing a fiber-reinforced thermoplastic resin prepreg, comprising laminating a film containing an amorphous thermoplastic resin and satisfying the following condition (1a) onto a carbon fiber substrate, heating the laminate to impregnate the carbon fiber substrate with the amorphous thermoplastic resin. Condition (1a) (v) The tensile elongation at break (T1) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (vi) Separately, the film is immersed in an oil solution containing 55-65% by mass of tributyl phosphate at 23°C for 1000 hours, and then the tensile elongation at break (T2) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (vii) The tensile elongation retention rate, calculated from the following formula (1), is 70% or higher. Tensile elongation retention rate = (Tensile elongation at break (T2) / Tensile elongation at break (T1)) × 100 ... (1)

[12] A fiber-reinforced thermoplastic resin prepreg comprising a matrix resin and carbon fibers, The matrix resin contains a polyetherimide resin (A) having repeating units represented by the following general formula (a), A fiber-reinforced thermoplastic resin prepreg in which the polyetherimide resin (A) content is 45 to 100% by mass relative to the total mass of the matrix resin.

[0030] [ka]

[0031] In equation (a), m is a number between 5 and 1500. [Effects of the Invention]

[0032] According to the present invention, a fiber-reinforced thermoplastic resin prepreg and a method for producing the same, as well as a molded article, can be provided, which yields a molded article with excellent chemical resistance and mechanical properties even when using an amorphous thermoplastic resin as the matrix resin. [Brief explanation of the drawing]

[0033] [Figure 1] This is a schematic diagram illustrating an example of a manufacturing apparatus for fiber-reinforced thermoplastic resin prepregs. [Modes for carrying out the invention]

[0034] [Fiber-reinforced thermoplastic prepreg] Hereinafter, an embodiment of the fiber-reinforced thermoplastic resin prepreg of the present invention (hereinafter also simply referred to as "prepreg") will be described. The prepreg of this embodiment includes a matrix resin and carbon fibers. The prepreg may further contain components other than the matrix resin and carbon fiber (optional components).

[0035] <Matrix resin> The matrix resin of this embodiment (hereinafter also simply referred to as the "resin composition") contains a polyetherimide resin (A) having repeating units represented by the following general formula (a) (hereinafter also referred to as the "repeating unit (a)"). If the matrix resin contains polyetherimide resin (A), the bending strength of the molded article obtained by molding the prepreg of this embodiment is increased, and the mechanical properties of the molded article are improved.

[0036] [ka]

[0037] In equation (a), m is a number between 5 and 1500. The proportion of repeating units (a) in 100% by mass of the polyetherimide resin (A) is preferably 50 to 100% by mass, more preferably 70 to 100% by mass, and even more preferably 95 to 100% by mass.

[0038] Polyetherimide resin (A) has a melt volume rate (MVR) of 3-10 cm³ as measured in accordance with ISO 1133. 3 It is preferable to include a polyetherimide resin (A-1) with a concentration of 10 min / min. If the polyetherimide resin (A) contains polyetherimide resin (A-1), the chemical resistance of the molded article will be improved. The set temperature for measuring the MVR of polyetherimide resin (A) was 360°C, and the load was 5 kg.

[0039] A commercially available polyetherimide resin (A-1) can be used, such as "Ultem (registered trademark; hereinafter the same) CRS5001" manufactured by SABIC Innovative Plastics. Polyetherimide resin (A-1) may be used alone or in combination of two or more types.

[0040] The polyetherimide resin (A-1) content is preferably 85% by mass or more, and more preferably 90% by mass or more, relative to the total mass of the matrix resin. Furthermore, the polyetherimide resin (A-1) content is preferably 95% by mass or less, relative to the total mass of the matrix resin. If the polyetherimide resin (A-1) content is above the lower limit, the chemical resistance of the molded article is further improved. If the polyetherimide resin (A-1) content is below the upper limit, the impregnation of the matrix resin into the carbon fibers can be well maintained.

[0041] Polyetherimide resin (A) has an MVR of 15-30 cm² at a set temperature of 360°C and a load of 5 kg, as measured in accordance with ISO 1133. 3It is preferable to further include a polyetherimide resin (A-2) which is 10 min / 10. Polyetherimide resin (A-2) has better fluidity than polyetherimide resin (A-1). Therefore, if polyetherimide resin (A) contains polyetherimide resin (A-2), the impregnation of the matrix resin into the carbon fibers is improved. As a result, the bending strength of the molded article is further increased, and the mechanical properties of the molded article are further improved.

[0042] Commercially available polyetherimide resins (A-2) can be used, such as "Ultem CRS5011" manufactured by SABIC Innovative Plastics. Polyetherimide resin (A-2) may be used alone or in combination of two or more types.

[0043] The polyetherimide resin (A-2) content is preferably 5% by mass or more relative to the total mass of the matrix resin. Furthermore, the polyetherimide resin (A-2) content is preferably 15% by mass or less, and more preferably 10% by mass or less, relative to the total mass of the matrix resin. If the polyetherimide resin (A-2) content is above the lower limit, the impregnation of the matrix resin into the carbon fibers is further enhanced. If the polyetherimide resin (A-2) content is below the upper limit, the chemical resistance and flexural strength of the molded article can be maintained well.

[0044] From the viewpoint of having an excellent balance between chemical resistance and impregnation properties, the polyetherimide resin (A) preferably contains polyetherimide resin (A-1) and polyetherimide resin (A-2). Furthermore, the polyetherimide resin (A) may further contain polyetherimide resins other than polyetherimide resin (A-1) and polyetherimide resin (A-2), as long as the effects of the present invention are not impaired. From the viewpoint of maintaining good chemical resistance of the molded article, the content of polyetherimide resin (A-3) is preferably 5% by mass or less, more preferably 1% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably substantially absent, relative to the total mass of the matrix resin. In this specification, "substantially absent" means not actively included, except for those included unintentionally.

[0045] From the viewpoint of maintaining good chemical resistance of the molded article, the content of polyetherimide resin (A) is preferably 95% by mass or more, more preferably 98% by mass or more, even more preferably 99% by mass or more, and particularly preferably 100% by mass, relative to the total mass of the matrix resin. The glass transition temperature (Tg) of polyetherimide resin (A) is preferably 50 to 500°C, more preferably 100 to 300°C, and even more preferably 150 to 250°C, from the viewpoint of fluidity and impregnation during molding. The glass transition temperature (Tg) is defined as the inflection point of the storage modulus measured by dynamic mechanical analysis (DMA).

[0046] The matrix resin may further contain a polyetherimide resin (B) other than polyetherimide resin (A), as long as it does not impair the effects of the present invention. Examples of polyetherimide resins (B) include those having repeating units represented by the following general formula (b) (hereinafter also referred to as "repeating unit (b)").

[0047] [ka]

[0048] In equation (b), n is a number between 5 and 1500. The proportion of repeating units (b) in 100% by mass of the polyetherimide resin (B) is preferably 10 to 100% by mass, more preferably 30 to 100% by mass, and even more preferably 50 to 100% by mass.

[0049] Commercially available polyetherimide resin (B) can be used, such as "Ultem 1000" and "Ultem 1010" manufactured by SABIC Innovative Plastics. Polyetherimide resin (B) may be used alone or in combination of two or more types.

[0050] From the viewpoint of maintaining good chemical resistance of the molded article, the content of polyetherimide resin (B) is preferably 5% by mass or less, more preferably 1% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably substantially absent, relative to the total mass of the matrix resin.

[0051] The matrix resin may further contain resins other than polyetherimide resin (hereinafter also referred to as "other resins"), as long as they do not impair the effects of the present invention. Other resins include polyamide (nylon 6, nylon 66, etc.) resins, polyolefin (polyethylene, polypropylene, etc.) resins, modified polyolefin resins, polyester (polyethylene terephthalate, polybutylene terephthalate, etc.) resins, polycarbonate resins, polyamide-imide resins, polyphenylene oxide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polystyrene resins, ABS resins, polyphenylene sulfide resins, liquid crystal polyester resins, and copolymers of acrylonitrile and styrene. Other resins may be used individually or in combination of two or more types.

[0052] From the viewpoint of maintaining good chemical resistance of the molded article, the content of other resins is preferably 1% by mass or less, more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably substantially absent, based on the total mass of the matrix resin.

[0053] The matrix resin satisfies the following condition (1). A higher tensile elongation retention rate under condition (1) indicates superior chemical resistance of the matrix resin. A tensile elongation retention rate of 15% or higher indicates particularly excellent chemical resistance of the matrix resin. A molded article with superior chemical resistance can be obtained from a prepreg containing a matrix resin with excellent chemical resistance. Condition (1) (i) The matrix resin is extruded into a film to produce a film, (ii) The tensile break elongation (T1) of the film in the direction perpendicular to the longitudinal direction (MD direction) (TD direction) is measured in accordance with JIS K 7127. (iii) Separately, the film prepared in (i) above is immersed in an oil solution containing 55-65% by mass of tributyl phosphate at 23°C for 1000 hours, and then the tensile elongation at break (T2) in the direction perpendicular to the longitudinal direction (MD direction) of the film (TD direction) is measured in accordance with JIS K 7127. (iv) The tensile elongation retention ratio, calculated from the following formula (1), is 15% or more and 90% or less. Tensile elongation retention rate = (Tensile elongation at break (T2) / Tensile elongation at break (T1)) × 100 ... (1)

[0054] From the viewpoint of further improving the overall chemical resistance of the molded article, the tensile elongation retention rate under condition (1) is preferably 80% or more, more preferably 85% or more, even more preferably 90% or more, particularly preferably 95% or more, and most preferably 100%. Among the chemical resistance of the molded article, from the viewpoint of the strength retention rate of the molded article in particular, the tensile elongation retention rate under condition (1) is preferably 15% or more, more preferably 20% or more. The tensile elongation retention rate under condition (1) is preferably 90% or less, and more preferably 85% or less. When the tensile elongation retention rate under condition (1) is 15% or more, the penetration of solvent into the molecular chains of the matrix resin is suppressed, so even when formed into a molded article, swelling of the matrix resin due to solvents, etc. is small, and changes in strength are less likely to occur. When the tensile elongation retention rate under condition (1) is 90% or less, the matrix resin is in a state in which it has a molecular-level free volume that can incorporate solvents, etc. between the resin chains, and the flow and impregnation of the matrix resin during molding proceed smoothly, so voids, etc. are less likely to be formed in the molded article. As a result, a high strength retention rate can be achieved during chemical resistance testing of the molded product. The tensile elongation retention rate under condition (1) can be controlled by the composition of the matrix resin. For example, the tensile elongation retention rate tends to increase as the content of polyetherimide resin (A-1) in the matrix resin increases.

[0055] The weight content of the matrix resin in the prepreg is preferably 15 to 70% by weight, more preferably 20 to 60% by weight, and even more preferably 25 to 45% by weight. If the weight content of the matrix resin is above the lower limit, sufficient adhesion between the carbon fibers and the matrix resin can be ensured. If the weight content of the matrix resin is below the upper limit, the reinforcing effect of the carbon fibers is fully exerted, and the bending strength of the molded article is further increased. In this specification, the weight content is a value obtained by a measurement method compliant with ASTM D3171 or JIS K7075.

[0056] The matrix resin may be a compound of two or more polyetherimide resins (A) having repeating units represented by the following general formula (a), each having a different melt volume rate measured in accordance with ISO 1133 at a set temperature of 360°C and a load of 5 kg. When two or more different polyetherimide resins (A) are included, one polyetherimide resin is designated as the "first polyetherimide resin," and the other polyetherimide resin having a smaller melt volume rate than the first polyetherimide resin is designated as the "second polyetherimide resin." From the viewpoint of film moldability and impregnation, the difference in melt volume rate expressed as [melt volume rate of the first polyetherimide resin] - [melt volume rate of the second polyetherimide resin] is preferably 5 to 27, more preferably 7 to 20, and even more preferably 10 to 15.

[0057] [ka]

[0058] In equation (a), m is a number between 5 and 1500.

[0059] Examples of the two or more polyetherimide resins included in polyetherimide resin (A) are the same as those described above for polyetherimide resin (A-1) and polyetherimide resin (A-2).

[0060] <Carbon fiber> While there are no particular restrictions on the type of carbon fiber, examples include polyacrylonitrile (PAN) carbon fiber, petroleum / coal pitch carbon fiber, rayon carbon fiber, and lignin carbon fiber. Among these, PAN carbon fiber is preferred. Continuous carbon fibers are preferred. Continuous fibers include, for example, carbon fibers in the form of a sheet or woven fabric (e.g., plain weave, twill weave, satin weave).

[0061] Carbon fibers are typically used in the form of carbon fiber bundles, which are bundles of multiple carbon fibers together. The number of filaments in the carbon fiber bundle is preferably 1,000 to 60,000, more preferably 1,000 to 50,000, and even more preferably 12,000 to 48,000. If the number of filaments in the carbon fiber bundle is within the above range, it exhibits excellent productivity and mechanical properties on an industrial scale.

[0062] The volume content (Vf) of carbon fibers in the prepreg is preferably 20 to 75 vol%, more preferably 30 to 70 vol%, and even more preferably 45 to 65 vol%. If the volume content (Vf) of carbon fibers is above the lower limit, the bending strength of the molded article will be higher. If the volume content (Vf) of carbon fibers is below the upper limit, sufficient adhesion between the carbon fibers and the matrix resin can be ensured. The volume content is a value obtained by a calculation method in accordance with ASTM D3171 or JIS K7075.

[0063] <Optional ingredients> The prepreg may contain fibers other than carbon fibers (hereinafter also referred to as "other fibers"). In this specification, carbon fibers and other fibers are collectively referred to as "reinforcement fibers." Other fibers that can be used include inorganic fibers other than carbon fibers, organic fibers, metallic fibers, or hybrid reinforcing fibers combining these. Other inorganic fibers besides carbon fibers include graphite fibers, silicon carbide fibers, alumina fibers, tungsten carbide fibers, boron fibers, and glass fibers. Examples of organic fibers include aramid fibers, high-density polyethylene fibers, and other general nylon fibers and polyester fibers. Examples of metal fibers include stainless steel and iron fibers. Examples of hybrid reinforcing fibers include carbon fibers coated with metal. Among these, glass fiber is preferred as the other fiber when considering the mechanical properties such as the strength of the prepreg. Other fibers may be used individually or in combination of two or more types. Other fibers are preferably continuous fibers.

[0064] The prepreg may further contain additives other than reinforcing fibers. Examples of additives include flame retardants, weather resistance modifiers, antioxidants, heat stabilizers, UV absorbers, plasticizers, lubricants, colorants, compatibilizers, and conductive fillers. Additives may be used individually or in combination of two or more types.

[0065] The volume content of additives in the prepreg is preferably 5% by volume or less, more preferably 1% by volume or less, and even more preferably 0.5% by volume or less, from the viewpoint of maintaining mechanical strength. Furthermore, the total volume content of the matrix resin, carbon fibers, other fibers, and additives in the prepreg is 100% by volume.

[0066] <Prepreg manufacturing method> The method for manufacturing prepregs is not particularly limited and can be manufactured by known methods. For example, prepregs can be manufactured by impregnating a carbon fiber substrate with a matrix resin. One method for impregnating the matrix resin is to process the matrix resin into a film with a thickness of approximately 10 to 100 μm, or into fibers with a fiber diameter of approximately 5 to 50 μm, or into a powder with an average particle size of approximately 10 to 100 μm, and then attach it to the carbon fiber substrate. Furthermore, "carbon fiber substrate" refers to an aggregate of carbon fibers.

[0067] If the prepreg contains additives, a matrix resin composition can be prepared by mixing the matrix resin with the additives, and this matrix resin composition can then be impregnated into the carbon fiber substrate. If the prepreg contains other fibers, the reinforcing fiber substrate containing carbon fibers and other fibers may be impregnated with a matrix resin or matrix resin composition. Furthermore, "reinforced fiber base material" refers to an aggregate of carbon fibers and other fibers.

[0068] The following describes one embodiment of a method for manufacturing prepregs. In the prepreg manufacturing method of this embodiment, a laminate is obtained by laminating a film containing a matrix resin and satisfying the following condition (1a) onto a carbon fiber substrate, and the laminate is heated to impregnate the carbon fiber substrate with the matrix resin to produce a prepreg. Specifically, using the manufacturing apparatus 10 shown in Figure 1, a carbon fiber substrate 11 is unwound from a roll 18. Separately, a film 12 satisfying the following condition (1a), unwound from multiple rolls 18, is laminated onto the upper and lower surfaces of the carbon fiber substrate 11 via a pressure roller 19 to form a laminate. After preheating with a heater 13, a release film 14 is placed on the upper and lower surfaces of the laminate. Next, the laminate is pressurized with a hot plate press 15 heated to above the melting point or flow temperature of the matrix resin, and then pressurized with a cooling press 16 cooled to below the solidification temperature to impregnate the carbon fiber substrate 11 with the matrix resin in the laminate. After that, the release film 14 is removed to obtain a prepreg 17. The heating temperature of the laminate is not particularly limited as long as it is the temperature at which the matrix resin is heated and melted. The range of the tensile elongation retention rate of the film in condition (1a) can be the same as that of the embodiments described above. For example, if the tensile elongation retention rate of the film is set to 70% or more and 100% or less, the film has high chemical resistance, which not only results in excellent chemical resistance for the molded article obtained by molding the prepreg, but also makes the prepreg less susceptible to chemical influences during the process of manufacturing the prepreg by layering the film on a carbon fiber substrate, thus stabilizing the quality of the prepreg. If the tensile elongation retention rate of the film is set to 15% or more and 90% or less, as described above, the strength retention rate of the molded article obtained by molding the prepreg obtained by the prepreg manufacturing method of this embodiment can be improved. The film to be laminated onto the carbon fiber substrate is obtained by extruding the matrix resin or matrix resin composition described above into a film. Condition (1a) (v) The tensile elongation at break (T1) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (vi) Separately, the film is immersed in an oil solution containing 55-65% by mass of tributyl phosphate at 23°C for 1000 hours, and then the tensile elongation at break (T2) in the direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127. (vii) The tensile elongation retention rate, calculated from the following formula (1), is 70% or higher. Tensile elongation retention rate = (Tensile elongation at break (T2) / Tensile elongation at break (T1)) × 100 ... (1)

[0069] Examples of prepreg forms include unidirectional prepregs (UD prepregs), which are sheet-like carbon fiber bundles with carbon fibers aligned in one direction and impregnated with matrix resin; cross prepregs, which are woven carbon fiber fabrics impregnated with matrix resin; and tow pregs, which are tows (carbon fiber bundles) that have been pre-impregnated with matrix resin. The thickness of the prepreg is preferably 0.04 to 0.7 mm, and more preferably 0.04 to 0.4 mm.

[0070] <Effects and Effects> The polyetherimide resin (A) described above is an amorphous thermoplastic resin, but it has repeating units (a), and the matrix resin containing this polyetherimide resin (A) satisfies condition (1). Therefore, with the prepreg of this embodiment, a molded article with excellent chemical resistance and mechanical properties can be obtained even while using an amorphous thermoplastic resin as the matrix resin. In particular, if polyetherimide resin (A) contains polyetherimide resin (A-1), chemical resistance is further improved. Furthermore, if polyetherimide resin (A) contains polyetherimide resin (A-2) in addition to polyetherimide resin (A-1), it offers an excellent balance between chemical resistance and impregnation properties.

[0071] The prepreg is not limited to the embodiments described above, and may, for example, include an amorphous thermoplastic resin, a matrix resin that satisfies condition (1) above, carbon fibers, and optional components as needed. Examples of amorphous thermoplastic resins include the polyetherimide resin, polyvinyl chloride resin, polystyrene resin, polymethyl methacrylate resin, polycarbonate resin, polyethersulfone resin, and polyamideimide resin mentioned above. These amorphous thermoplastic resins may be used individually or in combination of two or more. From the viewpoint of moldability, the content of amorphous thermoplastic resin is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, relative to the total mass of the matrix resin (resin composition). The content of amorphous thermoplastic resin can be 100% by mass or less, or 98% by mass or less, relative to the total mass of the matrix resin (resin composition). The carbon fibers and optional components are the same as those exemplified earlier. The prepreg of this embodiment can be manufactured, for example, by impregnating a carbon fiber substrate with a matrix resin containing an amorphous thermoplastic resin. The method for impregnating the matrix resin is the same as the method exemplified earlier. Instead of a matrix resin, a matrix resin composition containing a matrix resin and additives may be impregnated into the carbon fiber substrate. If the prepreg of this embodiment contains other fibers, a matrix resin or matrix resin composition may be impregnated into a reinforcing fiber substrate containing carbon fibers and other fibers.

[0072] Alternatively, for example, a prepreg may be produced by laminating a film containing an amorphous thermoplastic resin and satisfying the above condition (1a) onto a carbon fiber substrate, and then heating the resulting laminate to impregnate the carbon fiber substrate with the amorphous thermoplastic resin. The heating temperature of the laminate is not particularly limited as long as it is the temperature at which the amorphous thermoplastic resin melts. The film laminated onto the carbon fiber substrate is obtained by extruding an amorphous thermoplastic resin, or a matrix resin or matrix resin composition containing an amorphous thermoplastic resin, into a film.

[0073] Furthermore, the prepreg is not limited to the embodiments described above, and may, for example, include a matrix resin containing a polyetherimide resin (A) having repeating units represented by the general formula (a), carbon fibers, and optional components as needed. In the matrix resin of this embodiment, the content of polyetherimide resin (A) is 45 to 100% by mass relative to the total mass of the matrix resin, preferably 60 to 100% by mass, more preferably 70 to 100% by mass, even more preferably 80 to 100% by mass, particularly preferably 90 to 100% by mass, and most preferably 95 to 100% by mass. The matrix resin may contain resins other than the polyetherimide resin (A) (for example, the polyetherimide resin (B) described above, or other resins), as long as the effects of the present invention are not impaired. The carbon fibers and optional components are the same as those exemplified earlier. The prepreg of this embodiment can be manufactured, for example, by impregnating a carbon fiber substrate with a matrix resin containing a polyetherimide resin (A). The method for impregnating the matrix resin is the same as the method exemplified earlier. Instead of a matrix resin, a matrix resin composition containing a matrix resin and additives may be impregnated into the carbon fiber substrate. If the prepreg of this embodiment contains other fibers, a matrix resin or matrix resin composition may be impregnated into a reinforcing fiber substrate containing carbon fibers and other fibers.

[0074] [Molded body] The molded body is made by molding the prepreg described above, and is formed by laminating and integrating the prepreg. Preferably, the molded article is a molded article formed by laminating two or more prepregs of the above-described embodiment. However, the molded article may also be a molded article formed by laminating a combination of the prepreg of the above-described embodiment and other prepregs other than the prepreg of the above-described embodiment.

[0075] The lamination configuration of the prepregs in the laminate is not particularly limited. The number of prepreg layers in a laminate can be appropriately set according to the thickness of the prepreg and the required thickness of the molded body. When the prepreg is a UD prepreg, the fiber direction of the carbon fibers in each UD prepreg to be laminated can be appropriately set according to the physical properties required of the molded product. The fiber direction of the carbon fibers in each UD prepreg may be in the same direction. Furthermore, for example, if isotropy is required for the physical properties of the molded product, it is preferable to laminate each UD prepreg to be laminated so that the carbon fiber direction in a plan view is a combination of 0° and 90°, a combination of 0°, 45°, 90°, -45°, or a combination of 0°, 60°, -60°, with the layers being symmetrical in the thickness direction.

[0076] <Method for manufacturing molded articles> The molded product is obtained by molding a prepreg. The method for forming the prepreg is not particularly limited, but examples include forming a single prepreg sheet or a stack of multiple prepreg sheets using a die press, autoclave, hot or cold press, etc. One example of a prepreg lamination method is an automated lamination method using robots.

[0077] As the molded articles described above are formed by molding the aforementioned prepregs, they exhibit excellent chemical resistance and mechanical properties, even though amorphous thermoplastic resin is used as the matrix resin. [Examples]

[0078] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0079] [material] The matrix resins used in each example are shown below. • PEI(A-1): Polyetherimide resin having the repeating unit (a) (manufactured by SABIC Innovative Plastics, trade name "Ultem CRS5001", MVR: 7cm3 (10 minutes; set temperature: 360℃, load: 5kg, glass transition temperature: 225℃). • PEI(A-2): Polyetherimide resin having the repeating unit (a) (manufactured by SABIC Innovative Plastics, product name "Ultem CRS5011", MVR: 20cm 3 (10 minutes; set temperature: 360℃, load: 5kg, glass transition temperature: 225℃). • PEI(B): Polyetherimide resin having the repeating unit (b) (manufactured by SABIC Innovative Plastics, trade name "Ultem CRS1000", MVR: 13cm 3 (10 minutes; set temperature: 360℃, load: 5kg, glass transition temperature: 217℃).

[0080] [Measurement and Evaluation] <Evaluation of toughness: Measurement of tensile elongation at fracture> The film was cut to dimensions of 100 mm in length (TD) x 15 mm in width (MD) to prepare test specimens (0.05 mm thick). In accordance with JIS K 7127, the tensile elongation at break of the test specimen (film) in the direction perpendicular to the longitudinal direction (MD direction) (TD direction) was measured using a universal material testing machine (manufactured by Intesco Corporation, product name "MODEL205") under the conditions of a temperature of 23°C, relative humidity of 50%, tensile speed of 200 mm / min, and gripping distance of 50 mm. The tensile elongation at break was measured for five test specimens, and the average value was defined as the tensile elongation at break (T1) of the film before immersion in hydraulic fluid.

[0081] <Calculation of Tensile Elongation Retention Rate> The film was cut to a length (TD) of 100 mm and a width (MD) of 15 mm to prepare test specimens (thickness 0.05 mm). As the hydraulic fluid, we used an oil solution containing 55-65% by mass of tributyl phosphate (manufactured by Eastman Chemical, trade name "Skydrol LD4"). The test specimens were immersed in hydraulic fluid at 23°C for 1000 hours, then removed from the hydraulic fluid and left to stand for 24 hours in a 23°C atmosphere. Subsequently, in accordance with JIS K 7127, the tensile elongation at break of the test specimen (film) in the direction perpendicular to the longitudinal direction (MD direction) (TD direction) was measured using a universal material testing machine (manufactured by Intesco Corporation, product name "MODEL205") under the conditions of a temperature of 23°C, relative humidity of 50%, tensile speed of 100 mm / min, and gripping distance of 50 mm. The tensile elongation at break was measured for five test specimens, and the average value was taken as the tensile elongation at break (T2) of the film after immersion in hydraulic fluid. The tensile elongation retention rate was then calculated using the following formula (1). Tensile elongation retention rate = (Tensile elongation at break (T2) / Tensile elongation at break (T1)) × 100 ... (1)

[0082] <Evaluation of mechanical properties: Measurement of 90° bending strength> A molded body, laminated so that all fibers are oriented in the 0° direction, was cut to dimensions of 50 mm in length (perpendicular to the fibers) x 12.7 mm in width (parallel to the fibers) to prepare test specimens (2 mm thick). In accordance with ASTM D790, a universal testing machine (INSTRON, product name "INSTRON 5565") equipped with a 3-point bending jig (indenter R=5.0mm, support R=3.2mm) was used, with the ratio of the distance between supports (L) to the thickness of the test specimen (d) L / d=16, and the crosshead speed=(L 2 A three-point bending test was performed under the condition (×0.01) / (6×d), and the 90° bending strength was measured. The 90° bending strength was measured for six test specimens, and the average value was used as the 90° bending strength of the molded body.

[0083] <Evaluation of mechanical properties: Measurement of in-plane shear strength retention rate> A molded body, laminated with fibers oriented at +45° and -45°, was cut to dimensions of 230 mm in length and 25.4 mm in width, and twelve test specimens (3 mm thick) were prepared. In accordance with ASTM D3518, the in-plane shear strength was measured using a universal testing machine (INSTRON 5882, manufactured by INSTRON). The in-plane shear strength was measured for six test specimens, and the average value was defined as the in-plane shear strength (T3) of the molded body. The remaining six test specimens were immersed in hydraulic fluid at 23°C for 500 hours, then removed from the hydraulic fluid and left to stand in a 23°C atmosphere for 24 hours. Subsequently, the in-plane shear strength was measured in accordance with ASTM D3518 using a universal testing machine (INSTRON, product name "INSTRON 5882"). The in-plane shear strength was measured for all six test specimens, and the average value was taken as the in-plane shear strength (T4) of the molded body after immersion in hydraulic fluid. The retention rate of the in-plane shear strength was then calculated using the following formula (2). In-plane shear strength retention rate = (In-plane shear strength after immersion in hydraulic oil (T4) / In-plane shear strength (T3)) × 100 ... (2)

[0084] [Example 1] <Prepreg manufacturing> A matrix resin was prepared by dry-blending PEI(A-1) and PEI(A-2) in a mass ratio of 90:10. This matrix resin was kneaded at 380°C in a 40mm diameter single-screw extruder, then extruded into a film using a T-die. The film was rapidly cooled at approximately 200°C on a cast roll to produce a film with a thickness of 0.05mm. The tensile elongation at break was measured for the obtained films, and the tensile elongation retention rate was determined. The results are shown in Table 1.

[0085] A carbon fiber sheet made of PAN-based carbon fiber (manufactured by Mitsubishi Chemical Corporation, product name "MR50R", 570 tex, 12,000 strands) oriented in one direction was laminated with a previously prepared film, and the film was heat-melted and impregnated into the carbon fiber sheet to produce a prepreg. The resulting prepreg had a thickness of 0.2 mm, and the volume content (Vf) of carbon fibers, measured according to ASTM D3171, was 60 vol%.

[0086] <Manufacturing of molded products> Ten pieces of prepreg, each measuring 118mm x 198mm, were stacked so that all fibers were facing 0°, creating a laminate with a thickness of 2mm. The resulting laminate was placed in the lower die of a steel mold, and after closing the upper die, the mold was preheated to 340°C in approximately 10 minutes in a two-stage heating and cooling press (manufactured by Shinto Metal Industry Co., Ltd., product name "50-ton press") set to 380°C, and then compression molding was performed for 30 minutes under molding conditions of 5 MPa. After that, the mold was transferred to a press surface heated to 80°C and cooled to 200°C in approximately 2 minutes to obtain a molded body measuring 120 mm x 200 mm (thickness 2 mm). The 90° bending strength of the obtained molded body was measured. The 90° bending strength was 116 MPa.

[0087] [Example 2] Except for not using PEI(A-2), the prepreg and molded articles were manufactured in the same manner as in Example 1, and various measurements and evaluations were performed. The results are shown in Table 1. The 90° bending strength of the obtained molded body was measured. The 90° bending strength was 101 MPa. Additionally, sixteen sheets of prepreg cut to dimensions of 178mm x 328mm were laminated in a [+45 / -45]4s configuration to create a laminate with a thickness of 3mm. The resulting laminate was placed in the lower die of a steel mold, and after closing the upper die, the mold was preheated to 340°C in approximately 10 minutes in a two-stage heating and cooling press (manufactured by Shinto Metal Industries Co., Ltd., product name "50-ton press") set to 380°C, and then compression molding was performed for 30 minutes under molding conditions of 5 MPa. After that, the mold was transferred to a press surface heated to 80°C and cooled to 200°C in approximately 2 minutes to obtain a molded body measuring 180 mm x 330 mm (thickness 3 mm). The in-plane shear strength retention rate was measured for the obtained molded articles. The results are shown in Table 1.

[0088] [Example 3] Prepregs and molded articles were manufactured in the same manner as in Example 2, except that PEI(A-1) and PEI(A-2) were dry-blended in a mass ratio of 80:20, and various measurements and evaluations were performed. The results are shown in Table 1. The 90° bending strength of the obtained molded body was measured. The 90° bending strength was 100 MPa.

[0089] [Example 4] Prepregs and molded articles were manufactured in the same manner as in Example 1, except that PEI(A-1) and PEI(A-2) were dry-blended in a 50:50 mass ratio, and various measurements and evaluations were performed. The results are shown in Table 1. The 90° bending strength of the obtained molded body was measured. The 90° bending strength was 102 MPa.

[0090] [Example 5] Except for using PEI(B) as the matrix resin, prepregs and molded articles were manufactured in the same manner as in Example 2, and various measurements and evaluations were performed. The results are shown in Table 1. The 90° bending strength of the obtained molded body was measured. The 90° bending strength was 113 MPa.

[0091] [Table 1]

[0092] As is clear from Table 1, the films formed from the matrix resins used in Examples 1-4 exhibited superior chemical resistance compared to the film formed from the matrix resin used in Example 5. The in-plane shear strength retention rates for Examples 2 and 5 also reflected the chemical resistance of the films. Example 3, which incorporates PEI(A-1) and PEI(A-2), showed particularly high retention of in-plane shear strength. In Examples 1 and 4, the presence of PEI(A-1) suppresses changes in physical properties due to effects such as swelling, while the presence of PEI(A-2) reduces voids in the molded article (fiber-reinforced composite material), resulting in higher retention of in-plane shear strength than in Examples 2 and 5. Example 3 shows that while the film tensile strength retention rate is lower than that of Example 2, the in-plane shear strength retention rate of the molded body is higher, demonstrating superior chemical resistance as a molded body. Thus, the prepreg of the present invention can achieve both high chemical resistance and mechanical properties. [Industrial applicability]

[0093] The fiber-reinforced thermoplastic resin prepreg of the present invention allows for the production of molded articles with excellent chemical resistance and mechanical properties, even when using an amorphous thermoplastic resin as the matrix resin. Therefore, the fiber-reinforced thermoplastic resin prepreg and molded articles of the present invention are useful as components for sporting goods, automobiles, aircraft, industrial equipment, and the like. [Explanation of symbols]

[0094] 10 Manufacturing equipment 11 Carbon fiber substrate 12 film 13 Heater 14 Release film 15. Hot plate press 16 Cooling press 17 Prepreg 18 rolls 19 Crimping roller

Claims

1. The composite material includes a matrix resin made of a polyetherimide resin (A) having a repeating unit represented by the following general formula (a), and carbon fibers, The matrix resin of the prepreg satisfies the following condition (1): Condition (1) (i) extruding the matrix resin into a film; (ii) measuring the tensile elongation at break (T1) in a direction perpendicular to the longitudinal direction of the film in accordance with JIS K 7127; (iii) Separately, the film produced in (i) is immersed in an oil solution containing 55 to 65% by mass of tributyl phosphate at 23° C. for 1000 hours, and then the tensile elongation at break (T2) in a direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127; (iv) The tensile elongation retention calculated by the following formula (1) is 15% or more and 90% or less. Tensile elongation retention rate = (tensile elongation at break (T2) / tensile elongation at break (T1)) × 100 (1) 【Chemistry 1】 In formula (a), m is a number from 5 to 1,500.

2. The prepreg according to claim 1, wherein the polyetherimide resin (A) comprises a polyetherimide resin (A-1) having a melt volume rate of 3 to 10 cm3 / 10 min at a set temperature of 360°C and a load of 5 kg, as measured in accordance with ISO 1133.

3. The prepreg according to claim 2, wherein the content of the polyetherimide resin (A-1) is 85 mass% or more relative to the total mass of the matrix resin.

4. The prepreg according to claim 2 or 3, wherein the content of the polyetherimide resin (A-1) is 95 mass% or less based on the total mass of the matrix resin.

5. The prepreg according to any one of claims 1 to 4, wherein the polyetherimide resin (A) contains a polyetherimide resin (A-2) having a melt volume rate of 15 to 30 cm3 / 10 min at a set temperature of 360°C and a load of 5 kg, as measured in accordance with ISO 1133.

6. The prepreg according to claim 5, wherein the content of the polyetherimide resin (A-2) is 5 mass% or more relative to the total mass of the matrix resin.

7. The prepreg according to claim 5 or 6, wherein the content of the polyetherimide resin (A-2) is 15 mass% or less relative to the total mass of the matrix resin.

8. The prepreg according to any one of claims 1 to 7, wherein the carbon fibers are continuous fibers.

9. A molded body obtained by molding the prepreg according to any one of claims 1 to 8.

10. The method includes heating a laminate obtained by laminating a film containing an amorphous thermoplastic resin on a carbon fiber substrate to impregnate the carbon fiber substrate with the amorphous thermoplastic resin, The amorphous thermoplastic resin is a polyetherimide resin (A) having a repeating unit represented by the following general formula (a): The method for producing a prepreg, wherein the film satisfies the following condition (1a): Condition (1a) (v) measuring the tensile elongation at break (T1) in a direction perpendicular to the longitudinal direction of the film in accordance with JIS K 7127; (vi) Separately, the film is immersed in an oil solution containing 55 to 65% by mass of tributyl phosphate at 23° C. for 1000 hours, and then the tensile elongation at break (T2) in a direction perpendicular to the longitudinal direction of the film is measured in accordance with JIS K 7127; (vii) The tensile elongation retention calculated by the following formula (1) is 70% or more. Tensile elongation retention rate = (tensile elongation at break (T2) / tensile elongation at break (T1)) × 100 (1) 【Chemistry 2】 In formula (a), m is a number from 5 to 1,500.

11. The method for producing a prepreg according to claim 10, wherein the carbon fiber substrate is a sheet-like carbon fiber bundle in which carbon fibers are aligned in one direction.

12. A method for producing a prepreg as described in claim 10 or 11, wherein the content of the polyetherimide resin (A) is 85 mass% or more relative to the total mass of the amorphous thermoplastic resin.

13. The method for producing a prepreg described in any one of claims 10 to 12, wherein the amorphous thermoplastic resin is a blend of two or more types of polyetherimide resin (A) having different melt volume rates at a set temperature of 360°C and a load of 5 kg, measured in accordance with ISO 1133.

14. A prepreg including a matrix resin and carbon fibers, The matrix resin is a polyetherimide resin (A) having two or more repeating units represented by the following general formula (a), each of which has a different melt volume rate at a set temperature of 360° C. and a load of 5 kg, as measured in accordance with ISO 1133: 【Chemistry 3】 In formula (a), m is a number from 5 to 1,500.

15. The prepreg according to claim 14, wherein the matrix resin is a blend of a polyetherimide resin (A-1) having a repeating unit represented by the following general formula (a) and having a melt volume rate of 10 cm3 / 10 min or less at a set temperature of 360°C and a load of 5 kg, measured in accordance with ISO 1133, and a polyetherimide resin (A-2) having a repeating unit represented by the following general formula (a) and having a melt volume rate of 15 cm3 / 10 min or more at a set temperature of 360°C and a load of 5 kg, measured in accordance with ISO 1133: 【Chemistry 4】 In formula (a), m is a number from 5 to 1,500.

16. The prepreg according to claim 14 or 15, wherein a sheet-like carbon fiber bundle in which the carbon fibers are aligned in one direction is impregnated with the matrix resin.

17. The prepreg according to any one of claims 14 to 16, wherein the content of the polyetherimide resin (A) is 85 mass% or more relative to the total mass of the matrix resin.

18. A resin composition comprising a polyetherimide resin (A) having two or more repeating units represented by the following general formula (a), each of which has a different melt volume rate at a set temperature of 360° C. and a load of 5 kg, as measured in accordance with ISO 1133: 【Chemistry 5】 In formula (a), m is a number from 5 to 1,500.

19. The resin composition according to claim 18, wherein the polyetherimide resin (A) is blended with a polyetherimide resin (A-1) having a melt volume rate of 3 to 10 cm3 / 10 min at a set temperature of 360°C and a load of 5 kg, as measured in accordance with ISO 1133.

20. The resin composition according to claim 19, wherein the blending amount of the polyetherimide resin (A-1) is 85 mass% or more based on the total mass of the resin composition.

21. A film comprising the resin composition according to any one of claims 18 to 20.